Pengaruh Jenis Pelarut Dan Waktu Ekstraksi Dengan Metode Soxhletasi Terhadap Aktivitas Antioksidan Minyak Biji Alpukat (Persea Americana Mill.) - Pangan, Media (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2017)
This research was conducted in order to determine observe and obtain the type of this solvent and extraction time to produce oil avocado seed with the highest antioxidant activity. The experimental design used in research was a factorial completely randomized design which consisted of two factors. The first factor was the type of solvent consisting of n-hexan, isopropyl alcohol, and petroleum ether. The second factor was the extraction time consisting of 1, 2, and 3 hours. The treatment was repeated twice to obtain 18 units of the experiment. Data were analyzed with analysis of variance, followed by Duncan test. The results show that the solvent of isopropyl alcohol and extraction time 2 hours resulted highest antioxidant activity with total carotenoids 140.27 ppm, total tocopherol 218.75 ppm, the antioxidant activity ( carotene bleaching ) 83.33%, the antioxidant activity (DPPH) 54.52% and yield 16.39%.